Euroization Drivers and Effective Policy Response : An Application to the case of Albania - della Valle, Guido; Cabezon, Ezequiel; Kota, Vasilika; Veyrune, Romain (Washington, D.C. : International Monetary Fund, 2018)
This paper proposes a methodology to develop empirically based and theoretically consistent deeuroization policies. It is derived from the experience of Albania. The paper is the first attempt to provide an empirical measure of the optimal level of euroization. The results indicate that euroization is trending above the estimated measure in Albania, calling for deeuroization policies. In the long term, deeuroization requires maintaining the commitment to low and stable inflation in a context of greater exchange rate flexibility to encourage saving in local currency. In the short term, policies that mitigate the financial stability risk due to euroization contribute to deeuroization inasmuch as they make banking intermediation in euro less financially attractive to the public.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet